Academic Classrooms as Rational Communications: (Review of the Book of Narrative from Academic Classrooms: The Lived Experience of University Professors) - Gholam Reza Azari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Academic classrooms and the lived experience of university professors have been a major concern for many academic, educational, and training systems in Iran and elsewhere in the world. The importance and necessity of addressing classroom space are a valuable realm that can provide a variety of challenges for education experts and managers. Therefore, in this essay, the book "A Narrative of Academic Classrooms: The Lived Experience of University Professors" was attempted by Abbas Kazemi from the Institute for Cultural and Social Studies published in 1396.  Using descriptive-analytic analysis, the purpose of the present review is to identify the strengths and weaknesses of the book and make it more useful for the subsequent editions without any bias.  First, his work was introduced, and then the book was criticized in two aspects of form and content. At the end of the critique, the rational communication approach is considered as a communicative channel for the classroom with the argument that it can take a deeper look at the learning process. In the end, , suggestions are made to eliminate the shortcomings of this work.